The Influence of Company Growth, Profitability, Leverage, and Inflation on the Value of Energy Sector Companies - Intan Rizki Arinta Putri; I Gusti Ketut Agung Ulupui; Hera Kahirunnisa (PT. BATARI EDU CALYA, 2024)
This research aims to determine whether company growth (GPG), profitability (NPM), leverage (DER), and inflation (IHK) partially affect company value on the IDX. The period used in this research is three years, starting from 2020-2022. This research uses a quantitative approach and purposive sampling. The population in this research comprises all energy sector companies that were registered on the IDX during the 2020-2022 period. A total of 76 companies were selected as research samples. Data were analyzed using multiple linear regression analysis. The data analysis technique used in analysing data is EViews 13. Based on the results of the data analysis, there is a significant influence of profitability and leverage on company value, and an insignificant influence of company growth and inflation on company value on the Indonesian Stock Exchange.